Normalized CT Dose Index of the CT Scanners Used in the National Lung Screening Trial - Cody, Dianna D. (2010)
The National Lung Screening Trial (NLST) includes 33 participating institutions, which performed 75, 133 lung cancer screening CT exams from 26,724 subjects during 2002–2007. For trial quality assurance reasons, CT radiation dose measurement data were collected from all multidetector-row CT scanners used in the NLST. A total of 247 measurements on 96 multi-row detector scanners were collected using a standard CT dose index (CTDI) measurement protocol. The scan parameters employed in the measurements (tube voltage, mAs and detector-channel configuration) were set according to trial-protocol for average size subjects. The normalized CTDI(w) (computed as CTDI(w) /mAs) obtained from each trial-participating scanner was tabulated. This study demonstrated a statistically significant difference in normalized CT dose index among CT scanner manufacturers, likely due to design differences such as filtration, bow-tie design and geometry. Our findings also indicated a statistically significant difference in normalized CT dose index among CT scanner models within GE, Siemens, and Philips. We also demonstrated a statistically significant difference in normalized CT dose index among all models and all manufacturers. And, we demonstrated a statistically significant difference in normalized CT dose index from CT scanners among manufacturers when grouped by 4 or 8 data channels vs 16, 32, or 64 channels, suggesting improved dose efficiency in more complex scanners. Average normalized CT dose index values varied by almost a factor of two across all scanners from all manufacturers. This study was focused on machine specific normalized CT dose index; patient dose and image quality were not addressed.